PENGARUH DIKLAT, KEPEMIMPINAN DAN HUBUNGAN INDUSTRIAL TERHADAP KINERJA KARYAWAN - Priyamedha, A.A. Hastya; Supartha, Wayan Gede (E-Jurnal Manajemen, 2019)
The purpose of this study is to find out about education and training, leadership and industrial relations on employee performance. The population in this study were 158 people with the method of determining the sample using purposive sampling. Data analysis techniques use multiple linear regression. The results showed that education and training had a positive and significant effect on employee performance. Leadership has a positive and significant effect on employee performance. Industrial relations have a positive and significant effect on employee performance. Conducive and harmonious industrial relations practices create a calm work so as to minimize disruption and problems in the work environment. When industrial relations are well maintained there will be an increase in employee productivity. Increasing employee productivity will affect the improvement of company performance. Good company performance is better able to improve employee welfare. Keywords : training, leadership, industrial industrial relation, performance